Pengembangan Media Pembelajaran Mata Pelajaran Desain Grafis Percetakan Berbasis Web Pada Kelas XI SMK Negeri 4 Samarinda - Arif Harjanto; Arif Zuhdi Winarto; Abi Romadon (Institut Informatika dan Bisnis Darmajaya, 2023)
This study aims to provide an understanding of concepts and website learning in printing graphic design learning, along with the times, learning techniques and methods have shifted from traditional teacher-centered patterns to technology-based learning that places students as the main learner (student center). The type of research used is Research and Development (RnD), with the ADDIE development model (analysis, design, development, implementation, evaluation). The era of website-based andriod/desktop learning on the use of the internet as a learning motivator. Vocational high school graphic design teacher, Must be able to create and develop Android/mobile-based learning content in order to be able to attract students' interest during learning, because currently this is the media that students are most interested in and use in everyday life. Needs analysis techniques for making website-based media are software requirements (Windows 10 operating system, Google Sites, and CorelDrawX7), laptop hardware requirements (RAM4. AMD 8) Android hardware (minimum cellphone Helio P60, minimum RAM 1 GB). Data collection techniques with the method of observation, interviews, and questionnaires. The data analysis technique used is qualitative analysis and quantitative analysis. The research subjects involved were 3 media experts consisting of 3 Mulawarman University lecturers. The validators consisted of 1 material expert teacher for the subject of graphic design printing at SMK Negeri 4 Samarinda, and students of class XI DKV SMK Negeri Samarinda. While the object under study is the feasibility of website-based learning media for graphic design subjects, printing, sketching and illustration subject matter.The results of this study are 1)Learning Media Products for Web-Based Printing Graphic Design Subjects 2) The feasibility test can be seen from the results of the test questionnaire obtained by 3 media experts obtained an average value of109.67 which is included in the category of